2011
DOI: 10.1002/uog.8856
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of prenatal screening and psychological management of test decisions

Abstract: Objectives 1.31 (95% CI,). An increased level of knowledge was also associated with higher levels of wellbeing (adjusted linear coefficient 0.51 (95% CI,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
51
2
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(61 citation statements)
references
References 29 publications
3
51
2
3
Order By: Relevance
“…11,13,26,[28][29][30][31][32][33][34][35] Twenty-two studies were prospective, 12,28,[36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55] including cross-sectional, 41,42,49 quasi-experimental, 53 pilot, 50 and longitudinal study designs. 52 Of the RCTs, five involved an information or educational intervention, 28,29,[32][33][34] five randomised the screening offer, 11,13,26,30,35 and there was one decision aid trial.…”
Section: Summary Of Studiesmentioning
confidence: 99%
See 3 more Smart Citations
“…11,13,26,[28][29][30][31][32][33][34][35] Twenty-two studies were prospective, 12,28,[36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55] including cross-sectional, 41,42,49 quasi-experimental, 53 pilot, 50 and longitudinal study designs. 52 Of the RCTs, five involved an information or educational intervention, 28,29,[32][33][34] five randomised the screening offer, 11,13,26,30,35 and there was one decision aid trial.…”
Section: Summary Of Studiesmentioning
confidence: 99%
“…Three studies used the same cohort as in previous studies; 13,39,46 in subsequent studies the sample was stratified differently, 40 different measures were applied, 11 and additional validation data were reported. 45 Eight studies were conducted in continental Europe, 11,13,38,[43][44][45][46]53 and 14 were from the United Kingdom. 12,26,29,30,[32][33][34][35]37,[39][40][41]51,54 Seven studies were from Australia, 31,36,[48][49][50]52,55 three from the United States, 28,42,56 and one from Taiwan.…”
Section: Summary Of Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, studies showed that prenatal diagnosis provides pregnant women with information that may be associated with better psychological management. [9][10][11] The present study was conducted to assess level of awareness of Egyptian women in the reproductive age about prenatal screening for congenital malformations and to explore their attitude towards prenatal testing and termination of pregnancy if medically indicated. Moreover, factors that might be associated with acceptance including women's perceptions and beliefs were identified.…”
mentioning
confidence: 99%